Added Value of Dual-Time-Point 18F-FDG PET/CT With Delayed Imaging for Detecting Aortic Graft Infection. Issue 27 (July 2015) - Chang, Chih-Yung; Chang, Cheng-Pei; Shih, Chun-Che; Yang, Bang-Hung; Cheng, Cheng-Yi; Chang, Chi-Wei; Chu, Lee-Shing; Wang, Shyh-Jen; Liu, Ren-Shyan; Assadi., Majid
<x xml:space="preserve">Abstract</x> Abstract 18F-FDG PET/CT is a promising tool in detecting aortic graft infection. Present study investigated the value of dual-time-point 18F-FDG PET/CT imaging (DTPI) with delayed imaging in assessing aortic graft infection. Twenty-nine patients with suspected aortic graft infection were prospectively enrolled in this DTPI study. Two nuclear medicine physicians read all the images and achieved consensus about the measurement of maximal standardized uptake value (SUVmax) and grading of image quality. The percentages of SUVmax change between initial and delayed images were recorded as retention index (RI); sensitivity, specificity, and accuracy were calculated based on reference standard. All the 5 infected aortic grafts had positive RIs, which were generally higher than that of noninfected grafts. Those noninfected grafts had variable RIs. Seven patients had improved image quality in delayed imaging. DTPI with delayed image detected all the infected grafts with improved specificity (88%) and accuracy (90%), providing conspicuous delineation of the infected graft extent. In conclusion, noninfected aortic grafts had more variable RIs than infected ones. DTPI might be useful for detecting aortic graft infection, improving image quality, and enhancing delineation of the infected aortic grafts.